PERLINDUNGAN LAHAN PERTANIAN DALAM MENGANTISIPASI ALIH FUNGSI TANAH AKIBAT PENGADAAN TANAH BAGI PEMBANGUNAN - Subekti, Rahayu; Budyatmojo, Winarno (Faculty of Law, Universitas Sebelas Maret, 2015)
AbstractThe objective of research was to anticipate and to analyze the Farming Land Protection in Anticipating the Land Function Shift Due to Land Procurement for Development. The problem of farming land compensation is an urgent to organize recalling that land procurement cases for development occurs widely and results in reduced farming land leading to decreased food product. The research method employed in this research was juridical sociological one with descriptive approach. Considering the result of research: The construction toll road in Sragen Regency involved farming and non-farming lands. Compensation was so far given in the form of money, cash and carry, corresponding to the agreement between land procurement committee and land owner. The sustainable food farming land policy was accommodated through local legal instrument, Local Regulation Number 11 of 2011 about Spatial Layout of Sragen Regency Area in 2011-2031, within which there was farming allocation area. The local Government of Sragen Regency should make policy on sustainable food farming land control. AbstrakTujuan penelitian ini untuk mengetahui dan menganalisa Perlindungan Lahan Pertanian Dalam Men- gantisipasi Alih Fungsi Tanah Akibat Pengadaan Tanah Bagi Pembangunan. Persoalan kompensasi lahan pertanian merupakan hal yang urgen untuk ditata mengingat kasus-kasus pengadaan tanah untuk pembangunan banyak terjadi dan menyebabkan berkurangnya lahan pertanian sehingga akan mengu- rangi produk pangan. Metode penelitian yang digunakan dalam penelitian ini adalah yuridis sosiologis dengan pendekatan diskriptif. Berdasarkan hasil penelitian menunjukkan dalam Pembangunan jalan Tol di Kabupaten Sragen meliputi tanah pertanian dan tanah non pertanian . Pemberian ganti rugi se- lama ini di berikan dalam bentuk uang , cash dan carry sesuai dengan kesepakatan antara pihak panitia pengadaan tanah dengan pemilik tanah. Kebijakan lahan pertanian pangan berkelanjutan diakomodir melalui instrumen hukum Daerah yaitu Peraturan Daerah Nomor 11 Tahun 2011 tentang Rencana Tata Ruang Wilayah Kabupaten Sragen Tahun 2011-2031 , yang didalamnya terdapat kawasan peruntukan pertanian. Hendaknya Pemerintah Daerah Kabupaten Sragen perlu mengambil kebijakan pengendalian lahan pertanian pangan berkelanjutan